2014
DOI: 10.1542/peds.2014-0323
|View full text |Cite
|
Sign up to set email alerts
|

Grommets for Otitis Media With Effusion in Children With Cleft Palate: A Systematic Review

Abstract: BACKGROUND AND OBJECTIVE: No consensus has yet been reached with regard to the link between otitis media with effusion (OME), hearing loss, and language development in children with cleft palate. The objective of this study was to address the effectiveness of ventilation tube insertion (VTI) for OME in children with cleft palate. METHODS:A dual review process was used to assess eligible studies drawn from PubMed, Medline via Ovid, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 41 publications
5
69
0
Order By: Relevance
“…A 2014 systematic review identified that children with CP ± CL and otitis media with effusion who receive tympanostomy tubes have better long-term speech and language outcomes. 32 Children with CP need regular audiologic evaluation and otolaryngology assessment as part of cleft/craniofacial team care.…”
Section: Hearing and Otitis Media With Effusionmentioning
confidence: 99%
“…A 2014 systematic review identified that children with CP ± CL and otitis media with effusion who receive tympanostomy tubes have better long-term speech and language outcomes. 32 Children with CP need regular audiologic evaluation and otolaryngology assessment as part of cleft/craniofacial team care.…”
Section: Hearing and Otitis Media With Effusionmentioning
confidence: 99%
“…A recent systematic review by Kuo et al published in Pediatrics addressed the effects of VTI in children with cleft palate and OME with regard to patient-centered outcomes [109]. The review followed the protocol outlined in Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) to enable full and transparent assessment of the existing literature, in order to provide evidence-based information pertaining to the management of OME in children with cleft palate.…”
Section: Prisma-compliant Systematic Reviewmentioning
confidence: 99%
“…Non-radiation induced OME (e.g. OME induced by an infection in the upper respiratory tract) is commonly caused by temporary dysfunction of the Eustachian tube with regard to ventilation, and can usually be "cured" using conventional treatments [12,13]. In contrast, the generally acknowledged etiologies of post-irradiation OME are associated with direct and irreversible radiation-induced damage to the Eustachian tube, including scarring of the tubal opening, poor mucociliary function, and fibrosis of tube-associated muscles.…”
Section: Conventional Management Options and Limited Therapeutic Effectsmentioning
confidence: 99%